Adaptive Robot Language Tutoring Based on Bayesian Knowledge Tracing and Predictive Decision-Making - Schodde, Thorsten; Bergmann, Kirsten; Kopp, Stefan (2017 12th ACM/IEEE International Conference on Human-Robot Interaction (HRI, 2017)
In this paper, we present an approach to adaptive language tutoring in child-robot interaction. The approach is based on a dynamic probabilistic model that represents the inter-relations between the learner's skills, her observed behaviour in tutoring interaction, and the tutoring action taken by the system. Being implemented in a robot language tutor, the model enables the robot tutor to trace the learner's knowledge and to decide which skill to teach next and how to address it in a game-like tutoring interaction. Results of an evaluation study are discussed demonstrating how participants in the adaptive tutoring condition successfully learned foreign language words.